2002
DOI: 10.1074/jbc.m203616200
|View full text |Cite
|
Sign up to set email alerts
|

Low Intracellular Zinc Impairs the Translocation of Activated NF-κB to the Nuclei in Human Neuroblastoma IMR-32 Cells

Abstract: In the current work, we studied how variations in extracellular zinc concentrations modulate different steps involved in nuclear factor B (NF-B) activation in human neuroblastoma IMR-32 cells. Cells were incubated in media containing varying concentrations of zinc (1.5, 5, 15, and 50 M). Within 3 h, the intracellular zinc content was lower in cells exposed to 1.5 and 5 M, compared with the other groups. Low intracellular zinc concentrations were associated with the activation of NF-B, based on high levels of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 46 publications
6
109
0
Order By: Relevance
“…These transcription factors play important roles in controlling oxidative stress response and cell proliferation (50,51), and their inactivation of binding impairs the ability of the cell to respond to oxidative stress and damage. Mackenzie et al (52) have also demonstrated recently alterations in NF B activation with low intracellular zinc in human neuroblastoma IMR32 cells. However, the precise mechanisms by which zinc affects transcription factor binding remain unclear.…”
Section: Discussionmentioning
confidence: 94%
“…These transcription factors play important roles in controlling oxidative stress response and cell proliferation (50,51), and their inactivation of binding impairs the ability of the cell to respond to oxidative stress and damage. Mackenzie et al (52) have also demonstrated recently alterations in NF B activation with low intracellular zinc in human neuroblastoma IMR32 cells. However, the precise mechanisms by which zinc affects transcription factor binding remain unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Nuclear and cytosolic fractions were isolated as previously described (Dignam et al, 1983;Osborn et al, 1989), with minor modifications (Mackenzie et al, 2002). Total cell fractions were prepared as previously described (Muller et al, 1997), with slight modifications (Mackenzie et al, 2006b).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that a decrease in cellular zinc inhibits NF-kB-dependent gene expression. NF-kB nuclear translocation was impaired in association with a low rate of microtubule assembly in the zinc deficient cells (Mackenzie et al, 2002(Mackenzie et al, , 2006a. The activation of both, NF-kB and NFAT, involves the exposure of a NLS that targets the transcription factor to the nuclei.…”
mentioning
confidence: 99%
“…Nuclear fractions were isolated as previously described (35). For the EMSA, the oligonucleotides containing the consensus sequence of Nrf2 or SP-1 were end labeled with [c-32 P]-ATP using T4 polynucleotide kinase and purified using Chroma Spin-10 columns.…”
Section: Animal Treatmentmentioning
confidence: 99%